PENINGKATAN HASIL BELAJAR SISWA KELAS IV SD MUHAMMADIYAH 1 KUDUS MELALUI MODEL MAKE A MATCH PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Indriani, Dwi Aprilia; Setiadi , Gunawan; Rondli, Wawan Shokib (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
This research aims to determine the improvement in learning outcomes of fourth grade students at SD Muhammadiyah 1 Kudus by implementing the make a match learning model in Pancasila education subjects. This research is a type of Classroom Action Research (PTK) which was carried out in 2 cycles. The research design was prepared based on planning, implementation, observation and reflection. The subjects of this research were 18 grade IV students at SD Muhammadiyah 1 Kudus. Data collection techniques include observation, interviews, tests, and documentation. The data analysis techniques used include quantitative and qualitative data analysis. The research results showed that there was an increase in student learning outcomes by implementing the make a match model, in cycle I obtained a percentage of 72.22% of the criteria “good” and there was an increase in cycle II with a percentage of 88.88% of the criteria “very good”. Based on the research results, it can be concluded that the application of the make a match model in learning Pancasila education is able to improve the learning outcomes of class IV students at SD Muhammadiyah 1 Kudus.